Multiplex SNaPshot—a new simple and efficient CYP2D6 and ADRB1 genotyping method. Issue 1 (December 2016) - Ben, Songtao; Cooper-DeHoff, Rhonda; Flaten, Hanna; Evero, Oghenero; Ferrara, Tracey; Spritz, Richard; Monte, Andrew
Abstract Background Reliable, inexpensive, high-throughput genotyping methods are required for clinical trials. Traditional assays require numerous enzyme digestions or are too expensive for large sample volumes. Our objective was to develop an inexpensive, efficient, and reliable assay forCYP2D6 andADRB1 accounting for numerous polymorphisms including gene duplications. Materials and methods We utilized the multiplex SNaPshot® custom genotype method to genotypeCYP2D6 andADRB1 . We compared the method to reference standards genotyped using the Taqman Copy Number Variant Assay followed by pyrosequencing quantification and determined assigned genotype concordance. Results We genotyped 119 subjects. Seven (5.9 %) were found to beCYP2D6 poor metabolizers (PMs), 18 (15.1 %) intermediate metabolizers (IMs), 89 (74.8 %) extensive metabolizers (EMs), and 5 (4.2 %) ultra-rapid metabolizers (UMs). We genotyped two variants in the β1-adrenoreceptor, rs1801253 (Gly389Arg) and rs1801252 (Ser49Gly). The Gly389Arg genotype is Gly/Gly 18 (15.1 %), Gly/Arg 58 (48.7 %), and Arg/Arg 43 (36.1 %). The Ser49Gly genotype is Ser/Ser 82 (68.9 %), Ser/Gly 32 (26.9), and Gly/Gly 5 (4.2 %). The multiplex SNaPshot method was concordant with genotypes in reference samples. Conclusions The multiplex SNaPshot method allows for specific and accurate detection ofCYP2D6 genotypes andADRB1 genotypes and haplotypes. This platform is simple and efficient and suited for high throughput.